The Correlation of Competitive Anxiety and Mental Thoughness in Badminton Athlete with Disability - Zuan Anazmi Rambe; Hasnida Hasnida; Josetta Maria Remila Tuapattinaja (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Athlete with disability is profession carried out by someone with physical, mental, sensory, motoric and/or intellectual limitations who consistently participates in competitons an achieves in sports. Competitive anxiety influence by mental toughness that can interfere athlete performance in field, it happens to in athlete with disability. Previous research proposed several factors that can influence competitive anxiety such fear of fail, fear of injuiry, fear of social appraisal and mental toughness. This research aims to examine the correlation of competitive anxiety and mental thoughness in athlete with disability. The data collection method used was by athlete with disability at national Paralympic committee. This research aims to examine the correlation of competitive anxiety and mental thoughness in athlete with disability. The data collection method used was by athlete with disability at national Paralympic committee. Data analysis in this research used by Pearson Product Moment. Total samples in this study is n = 7. There are several types of disabilities in this study such as Length Leg Difference, Short Stature and Quadriplegic. This study uses a mental scale of Toughness Questionnaire (MTQ) as many as 30 items to measure the variables of mental toughness and competitive state anxiety inventory-2 (CSAI-2R) A total of 18 Aitem. This research show that mental toughness has a positive and significant correlation on competitive anxiety. The implications of this research for the coach, athlete disability organization